Perbandingan Kekerasan dan Kekuatan Tekan Paduan Cu â Sn 6% Hasil Proses Metalurgi Serbuk dan Sand Casting - Suwanda, Totok; Rahman, Muh Budi Nur; Ramdani, Deny Fajrur (Semesta Teknika, 2008)
Metal production by sand casting and powder metallurgy indicates the advantage of metal process technology. Bearing materials must have hardness and compressive strength properties to withstand wear and pressure load. Material porosity provides the space for lubricant. The lubrication will decrease the friction and keep temperature low. Low friction and low temperature will increase the life time of bearing. The goal of this research is to compare the hardness, compressive strength, macrostructure and microstructure between Cu-Sn 6% alloy produced by sand casting and by powder metallurgy. During sand casting process, the metal was melted in the furnace and then poured in to the sand mold, whilst in the powder metallurgy process; the metal powder was compacted in the metal mould and then heated to a temperature below its melting point (sintering process). In this research, the powder was compacted at 200 MPa and then sintered at 800Â° C for 45 minutes. The observation of the microstructure showed that the Cu-Sn 6% Â alloy produced by powder metallurgy possessed more porositythan produced by sand casting. The sand casting process produced the Cu-Sn 6% alloy with Brinell Hardness Number (BHN) of 47.97 kgf/mm2 and compressive strength of 680.8 MPa. The powder metallurgy process produced the Cu-Sn 6% alloy with Brinell Hardness Number (BHN) of 27.08 kgf/mm2 and compressive strength of 944.4 MPa.